LIVER’S HEMODYNAMIC CONDITIONS PURULENT-NECROTIC PROCESSES ON THE FOOT IN PATIENTS WITH DIABETES - Василюк, С. М.; Федорченко, В. М.; Гудивок, В. І.; Біцька, І. В.; Осадець, В. С. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
At 50 patients diabetic foot syndrome is investigated hemodynamics of a liver by a method rheohepatography. Control group was 25 healthy people. At diabetic foot syndrome in a stage is purulent changes of fabrics there were infringements hepatic hemodynamics. The complex treatment з by use long constant regional intraarterial infusion of medicinal substances in foot, not at all patients has improved hepatic hemodynamics.